Crab Fishery Resources of Podophthalmus vigil Fabricius Along Parangipettai Coast South East Coast of India - Soundarapandian, P (International Journal of Pharmaceutical & Biological Archive, 2013)
Crab Fishery Resources of Podophthalmus vigil Fabricius Along Parangipettai Coast South East Coast of India